Mapping Underexplored Theoretical Frameworks for Social Media–Mediated Knowledge Dissemination: A Systematic Literature Review - Nabil Muttaqin; Dio Lingga Purwodani; Dwi Soca Baskara (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study synthesizes findings from seven studies exploring the role of social media in knowledge dissemination across diverse domains. These studies reveal a heterogeneous theoretical landscape, with most employing well-established frameworks such as Knowledge Management, Theory of Complexity, Social Cognitive Theory, and sociomateriality in conjunction with structuration theory. Notably, two studies did not specify any theoretical framework, highlighting a gap and an opportunity for the application of alternative perspectives. The analysis identifies several underutilized theoretical approaches with significant potential: Complex Adaptive Systems for modeling non-linear and cross-platform knowledge flows; Actor-Network Theory for capturing the dynamics of human and non-human actors within socio-technical networks; Diffusion of Innovations for understanding patterns of knowledge spread and adoption; Boundary Object Theory for analyzing knowledge translation across social groups; and Institutional Theory for examining the organizational structures influencing social media usage. Each of these alternative approaches presents unique analytical advantages, although their application is often constrained by challenges such as intensive data requirements or methodological intricacies. The findings underscore that while current research tends to favor established and context-specific theories, the complexity of social media-mediated knowledge dissemination may be more effectively addressed through the integration of these underexplored theoretical lenses.